(untitled) - Short, Martin; 1950-; Seuss; Dr. (Dallas, TX, 2012)
"All creatures have skills that they use to get by and some of these skills are things you can try. Some creatures are jumpers. Consider the flea. If a flea were your size he could hurdle a tree! Rabbits sense danger before they can see it. They thump on the ground, so their neighbors can flee it. Speaking of danger, beware the big cats! Theyre tricky, theyre sneaky--and they dont all wear hats. Come join this adventure with Sally and Nick, and the Cat--hes a smart one (thats his special trick)!" --Container.
Big cats.
Keywords: Juvenile films; Jumping; Juvenile films; Rabbits; Animal locomotion; Juvenile films; Animals; Juvenile films; Brothers and sisters; Juvenile films; Cat in the Hat (Fictitious character); Juvenile films; Television series; Childrens television programs; Animated television programs; Educational television programs; Television series; Educational television programs; Childrens films; Animated television programs; Childrens television programs; Juvenile works